2008
DOI: 10.1080/19396360802415778
|View full text |Cite
|
Sign up to set email alerts
|

Births Resulting from Oocyte Cryopreservation Using a Slow Freezing Protocol with Propanediol and Sucrose

Abstract: The human mature oocyte is particularly sensitive to cooling and low temperatures in addition to freeze-thaw damage. The efficiency of oocyte cryopreservation including the pregnancy outcome is still low. The aim of our study is to briefly introduce our preliminary clinical results achieved with oocyte cryopreservation (CP). Our work focused on the use of a slow cooling procedure using the cryoprotectants propanediol (1.5 M) and sucrose (0.3 M). Following a short incubation of 4-6 hours thawed oocytes were inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…The survival rate achieved in the present study is similar to that previously observed with the 0.3 M sucrose method [7,15,16,[31][32][33][34][35][36][37] and the 0.2 M sucrose method [17,19,21]. In some of the above studies only oocytes with optimal morphology were cryopreserved [37,38] which is not the case in the present study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The survival rate achieved in the present study is similar to that previously observed with the 0.3 M sucrose method [7,15,16,[31][32][33][34][35][36][37] and the 0.2 M sucrose method [17,19,21]. In some of the above studies only oocytes with optimal morphology were cryopreserved [37,38] which is not the case in the present study.…”
Section: Discussionsupporting
confidence: 92%
“…This may be a consequence of the slower embryo development [13] and organelle damage [14] reported for this method. Although parameters such as reduced time between collection and cryopreservation [15] and assisted hatching of subsequent embryos [16] may result in some improvement, the clinical efficiency has remained low (reviewed in [11]). In contrast, modifying the sucrose concentration to 0.2 M during dehydration also increased survival [17][18][19][20] but implantation did not appear to be impaired [19,21] suggesting more potential [11] with this modification, although a reduced implantation rate relative to fresh oocytes has also been reported recently [20].…”
Section: Introductionmentioning
confidence: 98%
“…In our study, after slow controlled-rate freezing, an overall survival rate of 70% was obtained, which is consistent with other published reports (21)(22)(23)(24)(25). Because most of the donated human oocytes were immature, we compared their freezing at different developmental stages of maturation to verify the optimal stage for cryopreservation.…”
Section: Discussionsupporting
confidence: 92%
“…For our freezing protocol, we chose a combination of PrOH and raffinose which are respectively penetrating and non-penetrating cryoprotectants. The use of PrOH in clinical freezing protocols gives rise to the birth of healthy babies following cryopreservation of both embryos and mature oocytes [3,26,44]. Human ovarian tissue cryopreserved with PrOH as cryoprotectant exhibits a satisfactory morphological preservation of follicles in comparison with fresh tissue [11,14].…”
Section: Discussionmentioning
confidence: 99%